Spatial Analysis of Urban Sprawling with an Emphasis on Ecological Infrastructure Integrity (Case Study: Miandoab City) - Sayedeh Alemohammad; Saeedeh Nasehi; Ali Asghar Alemohammad; Majid Ramezani Mehrian; Reza Farhadi (Environmental Energy and Economic Research, 2024)
The sprawling growth of urban settlements is a dominant spatial process in many cities of developing countries. This development's most severe apparent effect is the loss of ecological infrastructure. In this way, consequently, the ecosystem services that have been provided for human settlements for thousands of years will be lost. Urban ecological infrastructure is also very effective in climate change and energy consumption. This research aims to spatially analyze the sprawling growth of Miandoab City with an emphasis on ecological infrastructures. In this regard, first, land cover maps have been prepared. Then the future land cover is simulated and predicted by the CA-MARKOV chain method. Also, the metrics of the number of patches, the patch size, and the patch cohesion of spots have been calculated for all land cover types in the landscape. In addition, the urban expansion intensity in different directions and changes in the density of built land cover have been estimated. According to the findings, Miandoab City has experienced a very sprawling growth until 2023, during which the structural integrity of green infrastructure and bare lands has been severely destroyed in favor of built land cover. The direction of physical-spatial development of the city has been towards the eastern suburbs. Most of the bare lands and intensive growth potential are in these areas. Solutions with three strategies (protective, defensive, and opportunistic) have been presented for balancing physical-spatial development and increasing urban and extra-urban ecological infrastructure integrity.